Effects of Wood Meal Particle Size and Polyethylene Glycol 400 Content on Glycol Lignin Production - Takayuki Suzuki; Thi Thi Nge; Yusuke Matsumoto; Tatsuhiko Yamada (BioResources)
Glycol lignin (GL) produced via acidic solvolysis of cedar wood meal with polyethylene glycol (PEG) is a highly functional material. In this study, the effects of wood meal particle size and amount of PEG added on the properties of PEG400-modified GLs (GL400s) were examined. For this purpose, cedar wood meal with four different particle sizes ranging between 0.18 and 2.00 mm and PEG400 at liquid ratios of 5 and 3 with respect to the wood meal were used. Acidic solvolysis at 140 °C successfully decreased the amount of solid residue with increasing GL400 yield and reaction time at both liquid ratios of 5 and 3. Overall, wood meal size remarkably affected the physical properties of GL400s at low PEG400 content (liquid ratio 3). In addition, the glass transition temperature Tg and thermal flow temperature Tf increased with decreasing wood meal size. Consequently, GL400s with varying thermal properties (Tg = 63 to 97 °C, Tf = 109 to 149 °C) were successfully prepared by adjusting the PEG400 liquid ratios and wood meal size. The data will support the development of a stable manufacturing process for the mass production of GL.